Mycological and Genomic Characterization of Fusarium vorosii, a Potentially Pathogenic Fungus, Isolated from Field Crops and Weeds in Korea - Eunji Jeong; Jae Yun Lim; Jeong-Ah Seo (The Plant Pathology Journal)
Fusarium vorosii (Fv) is one of the least studied species of the Fusarium graminearum species complex, a major plant pathogen causing Fusarium head blight (FHB) in a variety of crops. In this study, we isolated 12 strains of Fv from cereal samples with FHB symptoms and gramineous weeds. Trichothecene genotyping of Fv strains showed that 10 strains were nivalenol (NIV) type and 2 strains were 15-acetyldeoxynivalenol (15ADON) type. Fv strains have similar mycological characteristics to Fusarium asiaticum, a major FHB pathogen of rice in Asia, however, asexual sporulation was at least 100 to 1,000 times higher in Fv. In comparison of pathogenicity, the Fv-15ADON type was more pathogenic than the NIV type in both rice and wheat, and had a similar level of pathogenicity as the F. asiaticum-NIV type. Among the 12 Fv strains, two representative ones, Fv-NIV type RN1 and Fv-15ADON type W15A1, were selected and their whole genomes were sequenced and analyzed. Complete genome sequences of two Fv strains, RN1 and W15A1, were assembled at the chromosome level with high quality compared to known Fv genomes. The genome data of the two Fv strains were compared with the reference strains already known. As a result of comparative genome analysis, it was found that they are phylogenetically related according to the trichothecene biosynthetic gene cluster, that is, toxin chemotype. Through this study, we provided important information about Fv species that can be potential pathogens in domestic crops about biological and genomic characteristics.